The Polish elections to the European Parliament in 2014 as shown in the Polish press - Barabasz, Adam (Rocznik Integracji Europejskiej, 2014)
The paper presents the opinions of Polish journalists on the results of the elections to the European Parliament in Poland in 2014. The paper discusses the style of the election campaigns conducted by the different political parties. It also assesses the degree to which politicians and society were involved in the European elections. The paper presents the profiles of EP members published in the Polish press. The analysis is conducted on the basis of articles published from April 15 till May 27, 2014 in “Gazeta Wyborcza”, “Rzeczpospolita”, “Zielony Sztandar”, “Przegląd”, “Gazeta Polska”, “Najwyższy Czas”, “Polityka”, “Wprost” and “Newsweek”.